A roadmap for high‐throughput sequencing studies of wild animal populations using noninvasive samples and hybridization capture. (20th April 2019) - White, Lauren C.; Fontsere, Claudia; Lizano, Esther; Hughes, David A.; Angedakin, Samuel; Arandjelovic, Mimi; Granjon, Anne‐Céline; Hans, Jörg B.; Lester, Jack D.; Rabanus‐Wallace, M. Timothy; Rowney, Carolyn; Städele, Veronika; et al.
Abstract: Large‐scale genomic studies of wild animal populations are often limited by access to high‐quality DNA. Although noninvasive samples, such as faeces, can be readily collected, DNA from the sample producers is usually present in low quantities, fragmented, and contaminated by microorganism and dietary DNAs. Hybridization capture can help to overcome these impediments by increasing the proportion of subject DNA prior to high‐throughput sequencing. Here we evaluate a key design variable for hybridization capture, the number of rounds of capture, by testing whether one or two rounds are most appropriate, given varying sample quality (as measured by the ratios of subject to total DNA). We used a set of 1, 780 quality‐assessed wild chimpanzee ( Pan troglodytes schweinfurthii ) faecal samples and chose 110 samples of varying quality for exome capture and sequencing. We used multiple regression to assess the effects of the ratio of subject to total DNA (sample quality), rounds of capture and sequencing effort on the number of unique exome reads sequenced. We not only show that one round of capture is preferable when the proportion of subject DNA in a sample is above ~2%–3%, but also explore various types of bias introduced by capture, and develop a model that predicts the sequencing effort necessary for a desired data yield from samples of a given quality. Thus, our results provide a useful guide and pave a methodological way forward for researchers wishing to plan similar hybridization capture studies.